Enhancement of γ-aminobutyric acid in a fermented red seaweed beverage by starter culture Lactobacillus plantarum DW12 - Ratanaburee A. (2014)
Lactobacillus plantarum DW12, a gamma-aminobutyric acid (GABA) producing strain, was used as a starter culture to produce a functional fermented red seaweed beverage (FSB). Optimal conditions for producing FSB were established using Central Composite Design by varying the amounts of monosodium glutamate (MSG), sucrose and the initial pH in MRS medium. After a verification test, 1% MSG, 6% sucrose and an initial pH of 6 were selected. Four treatments were tested: traditional formula (A), red seaweed-cane sugar-potable water = 3:1:10, w/w/v, initial pH 6; the traditional formula with a 5% starter culture consisting of 4.1 x 109 CFU of DW 12/ml (B); formula A modified by changing the amounts of cane sugar and MSG to 6% and 1%, respectively (C); formula C with a 5% starter culture added (D). Comparison among the 4 treatments showed that the treatment D produced the highest amount of GABA (4000 mg/L) during days 45-60 while the GABA content of A, B and C treatments was 340, 730 and 1690 mg/L, respectively. However, the results of the sensory test for the treatments C and D showed that the presence of MSG produced an unsatisfactory salty taste. All finished products from the 4 treatments met Thai standard guidelines for chemical and microbiological qualities after 120 days. The results indicated that enrichment of the GABA content in FSB is possible by adding MSG and the GABA producing strain DW12; however, the appropriate amount of MSG addition should be further studied. © 2011 by Pontificia Universidad Católica de Valparaíso, Chile.